Advances of electro-freezing in food processing - Jha, Piyush Kumar; Xanthakis, Epameinondas; Jury, Vanessa; Havet, Michel; LeBail, Alain (My University, 2018)
Food freezing is a complex process, involving heat transfer and a series of physical and chemical changes which may profoundly affect the product quality. Several novel freezing methods have been developed in recent times taking into account the energy saving and/or quality preservation to a greater extent upon thawing. Electro-freezing technique, especially electric field assisted freezing is gaining momentum among them; it offers less energy intensive freezing conditions (higher set point ambient temperature, lower air velocity), and allows better quality retention. In the present short review article, a focused overview of the main findings and the latest studies regarding the applications of electro-freezing in food is given.
Keywords: Freezing; Ice crystal size; Electro-freezing